Stubborn Gender Gaps in Paraguay’s Labor Market - Ruppert Bulmer, Elizabeth (World Bank, Washington, DC, 2019)
This note analyzes household survey data and firm-level data to measure gender gaps in employmentoutcomes over the past 15 years and shed light on the degree to which economic growth has translated into more and better jobs for men and women, and the relative impact on each group. The analysis relies primarily on micro-level data from the annual Encuesta Permanente de Hogares for 2001 through 2016, the Encuesta Continua de Empleo for 2010-2014, the Censo Economico 2011, a census of firms, and the 2015-16 Encuesta de Empresas, a follow-up firm survey. Patterns in labor supply and its correlates will be examined using household-level data, and the analysis will consider how gender and other worker characteristics are related to labor market outcomes. In addition, this note explores the degree to which private sector labor demand and firm productivity differ by gender; this is done using firm-level data to examine the drivers of firm performance and employment growth. The remainder of this note is structured as follows. Section 2 examines recent socio-demographic trends that have affected the number of women entering the labor market in Paraguay. Section 3 looks at gender differentials in labor market outcomes relating to work status, sector of employment and earnings, inter alia. Section 4 considers the gender composition of labor demand by private sector firms, and section 5 concludes with a discussion of policy options for the future.